2003
DOI: 10.1186/1472-6793-3-13
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of amylin release from cultured rabbit gastric fundic mucosal cells

Abstract: BackgroundAmylin (islet amyloid polypeptide) is a hormone with suggested roles in the regulation of glucose homeostasis, gastric motor and secretory function and gastroprotection. In the gastric mucosa amylin is found co-localised with somatostatin in D-cells. The factors regulating gastric amylin release are unknown. In this study we have investigated the regulation of amylin release from gastric mucosal cells in primary culture. Rabbit fundic mucosal cells enriched for D-cells by counterflow elutriation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Lines with dual inhibition and arrow signs indicate evidence for both directions of effects. Supporting literature for the pathways illustrated here that is not highlighted elsewhere in this review can be found here: (1; 4; 5; 14; 43; 53; 57; 163; 201; 202). …”
Section: Figurementioning
confidence: 99%
“…Lines with dual inhibition and arrow signs indicate evidence for both directions of effects. Supporting literature for the pathways illustrated here that is not highlighted elsewhere in this review can be found here: (1; 4; 5; 14; 43; 53; 57; 163; 201; 202). …”
Section: Figurementioning
confidence: 99%
“…( 11 ) Insulin has a satiety effect on the central nervous system, while amylin decreases gastric emptying, due to vagal action. ( 12 )…”
Section: Introductionmentioning
confidence: 99%